2017
DOI: 10.1371/journal.pone.0168584
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diabetes Related Complications with Heart Rate Variability among a Diabetic Population in the UAE

Abstract: Microvascular, macrovascular and neurological complications are the key causes of morbidity and mortality among type II diabetes mellitus (T2DM) patients. The aim of this study was to investigate the alterations of cardiac autonomic function of diabetic patients in relation to three types of diabetes-related complications. ECG recordings were collected and analyzed from 169 T2DM patients in supine position who were diagnosed with nephropathy (n = 55), peripheral neuropathy (n = 64) and retinopathy (n = 106) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…Mohammedi et al [ 45 ] demonstrated that the presence of microvascular (including peripheral neuropathy) or macrovascular disease at baseline is independently associated with an increased risk of major clinical micro- and macrovascular events and death in patients with type 2 diabetes. Khandoker et al [ 46 ] revealed that peripheral neuropathy and other microvascular complications could affect heart rate variability. The previous study and our present results imply that DPN and other diabetic vascular complications are interconnected.…”
Section: Discussionmentioning
confidence: 99%
“…Mohammedi et al [ 45 ] demonstrated that the presence of microvascular (including peripheral neuropathy) or macrovascular disease at baseline is independently associated with an increased risk of major clinical micro- and macrovascular events and death in patients with type 2 diabetes. Khandoker et al [ 46 ] revealed that peripheral neuropathy and other microvascular complications could affect heart rate variability. The previous study and our present results imply that DPN and other diabetic vascular complications are interconnected.…”
Section: Discussionmentioning
confidence: 99%
“…This allows looking at the high correlation between independent variables (usually 0.50 and above), as such one of the highly correlated variables was dropped before the Model analysis. The BLR was chosen due to dependent variable was made dichotomous; high REA-ECD acceptance=1 (Khandoker et al, 2017;Copas, 1983;Altman & Andersen, 1989;Derksen & Keselman, 1992;Huguet et al, 2017). BLR choice was also due to independent variables were on different measurements.…”
Section: Sample Sizes Determinants Population Sizementioning
confidence: 99%
“…Since the autonomic nervous system (ANS) innervates vascular walls, regulating wall contractility and tension, alterations in this control manifest as detrimental effects on endothelial and vascular function, favouring atherogenesis (Chistiakov et al, 2015;Grassi et al, 2015). Impairments in the ANS and vascular function frequently coexist in the pathogenesis of different cardiovascular diseases, such as myocardial infarction (Gautier et al, 2007;Khandoker et al, 2017;Sessa et al, 2018) and stroke (Bots et al, 1996;O'Leary et al, 1999;Kwon et al, 2008), reflecting a complexity relationship. Autonomic activity can be easy and noninvasively assessed through its action on the cardiovascular system, named heart rate variability (HRV) analysis (Task Force of ESC & NASPE, 1996;Ulleryd et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Impairments in the ANS and vascular function frequently coexist in the pathogenesis of different cardiovascular diseases, such as myocardial infarction (Gautier et al , ; Khandoker et al , ; Sessa et al , ) and stroke (Bots et al , ; O'Leary et al , ; Kwon et al , ), reflecting a complexity relationship. Autonomic activity can be easy and noninvasively assessed through its action on the cardiovascular system, named heart rate variability (HRV) analysis (Task Force of ESC & NASPE, ; Ulleryd et al , ).…”
Section: Introductionmentioning
confidence: 99%